Fuzzy controller for frequencyregulation on micro-hydro power plant [electronic resource] - 533958 Ken Hensley Anak Giki; Azhar Khairuddin (2011)
Project Paper (Sarjana Muda Kejuruteraan (Elektrik)) - Universiti Teknologi Malaysia, 2011